Energy and exergy analyses of coal gasification with supercritical water and O2-H2O. (5th February 2019) - Chen, Zhewen; Gao, Lin; Han, Wei; Zhang, Longyan
Highlights: Coal gasification in supercritical water and O2 -H2 O are basically compared. The exergy destruction and distribution of the technologies are analyzed. Coal gasification in supercritical water has thermodynamic advantages. Abstract: Supercritical water can cleanly and efficiently convert coal into hydrogen-rich syngas. The supercritical water coal gasification (SCWG) technology is compared with O2 -H2 O coal gasification technology from the aspects of cold gas efficiency (CGE) and exergy efficiency (EE). The graphical exergy analyses (EUD methodology) were adopted to the key processes or units in the gasification technologies. The results showed that when the coal-water-slurry concentration (CWSC) is higher, the CGE and EE of the SCWG technology are higher than that of the O2 -H2 O coal gasification technology. The origins of the exergy destructions in the gasification technologies were analyzed. The heating of water lead to the maximum exergy destructions in the gasification technologies, which account for approximately 40.21% and 53.57% of the total exergy destruction in the gasifier.